Setīañcala-digdarśana : vividha anusandhānātmaka vishayasamanvita - Nepāla, Pūrṇa Prakāśa (Nepāladarśana ra vāṅmaya paridarśanakālāgi upayogī svadeśadarśana pushpahāra, 1978)
Geographical and cultural accounts of the Seti Zone of Nepal; includes biographical sketches of eminent personalities of the area.